Empleo y desempleo: un análisis de la elaboración de estadísticas - Garavito, Cecilia (1999)
The series of .employment and unemployment are fundamental pieces for the analysis of the effects of the economic policy on the well being of households. The divergence between which the public perceives like a problem of lack of employment and what the government affirms, that the problem is only one of low income, makes it necessary to review these series. Two are the problems mentioned on the quality of the series in our country. In the first place, the almost continuous growth of employment as measured by the series obtained from the National Survey of Households. (NSH), as opposed to the descend of the employment in the modern sector, measured by the series obtained from the Survey of Variation of Employment (SVE). Reasons that could be explaining this divergence to a certain extent are: differences in the universes of the sources used, faults in the registration of temporary employment and changes in the questionnaires of the surveys, the sample cover and its design. Secondly, the little variation of the rate of open unemployment and its low level, which would be explained by slants in the processing of the NSH, by the way to measure the indicator, and by the problem not yet solved of hidden unemployment.